Estimation of ground reaction forces from kinematics in ski-jumping imitation jumps - Schwameder, H.; Kröll, J.; Lindorfer, J.; Fritz, J. (ISBS Proceedings Archive (Michigan), 2019)
The purpose of the study was to determine the accuracy and the precision of calculated forces based on inverse dynamics during imitation jumps by comparing the results with force plate data. Ten ski-jumpers performed four imitation jumps on a force plate. Additionally, the vertical ground reactions forces were calculated based on an inverse dynamics (ID) approach using kinematic data from a motion capture system. The average accuracy and precision was found to be 60 N and ± 20 N for the peak vertical force, respectively, and -0.3 cm and ±1.6 cm, respectively, for the average jump height. The mean values for jump height were, respectively. The ID approach is assessed to be feasible for the estimation of vertical ground reaction forces exclusively from kinematic data with sufficient accuracy and precision so it can be used for the development of a universal diagnostics tool for ski-jumping imitation jumps.